Functional investigation of two simultaneous or separately segregating DSP variants within a single family supports the theory of a dose‐dependent disease severity. Issue 6 (1st April 2022) - Vermeer, Mathilde C. S. C.; Andrei, Daniela; Kramer, Duco; Nijenhuis, Albertine M.; Hoedemaekers, Yvonne M.; Westers, Helga; Jongbloed, Jan D. H.; Pas, Hendri H.; van den Berg, Maarten P.; Silljé, Herman H. W.; van der Meer, Peter; Bolling, Maria C.
Abstract: Desmoplakin (DP ) is an important component of desmosomes, essential in cell–cell connecting structures in stress‐bearing tissues. Over the years, many hundreds of pathogenic variants in DSP have been associated with different cutaneous and cardiac phenotypes or a combination, known as a cardiocutaneous syndrome. Of less than 5% of the reported DSP variants, the effect on the protein has been investigated. Here, we describe and have performed RNA, protein and tissue analysis in a large family where DSP c.273+5G>A/c.6687delA segregated with palmoplantar keratoderma (PPK), woolly hair and lethal cardiomyopathy, while DSP WT/c.6687delA segregated with PPK and milder cardiomyopathy. hiPSC‐derived cardiomyocytes and primary keratinocytes from carriers were obtained for analysis. Unlike the previously reported nonsense variants in the last exon of DSP that bypassed the nonsense‐mediated mRNA surveillance system leading to protein truncation, variant c.6687delA was shown to cause the loss of protein expression. Patients carrying both variants and having a considerably more severe phenotype were shown to have 70% DP protein reduction, while patients carrying only c.6687delA had 50% protein reduction and a milder phenotype. The analysis of RNA from patient cells did not show any splicing effect of the c.273+5G>A variant. However, a minigene splicing assay clearly showed alternative spliced transcripts originating from this variant. This study shows the importance of RNA and protein analyses to pinpoint the exact effect of DSP variants instead of solely relying on predictions. In addition, the particular pattern of inheritance, with simultaneous or separately segregating DSP variants within the same family, strongly supports the theory of a dose‐dependent disease severity.